EFFICIENCY OF TRAINING COURSES IN LAPAROSCOPIC SURGERY FOR MEDICAL STUDENTS - Dobromir Dimitrov; Martin Karamanliev; Tsvetomir Ivanov; Nadya Stanislavova; Tashko Deliyski; Slavcho Tomov (Peytchinski Publishing, 2019)
Purpose: In recent decades, laparoscopic surgery (LS) has become a standard in the treatment of many diseases and is increasingly preferred by patients, therefore the need for specific training. In Bulgaria, there is a lack of regular real-time minimally invasive surgery training for students and young doctors specializing in surgical specialities. Aim: Our aim is to evaluate the influence and efficiency of extra-curricular laparoscopic surgery courses organized at Medical University of Pleven, Bulgaria and the need for similar courses in medical students' training. Methods: Anonymous poll in Google forms was sent at least 1 year after the completion of the training course to all of the 60 participants in the courses from 2013 to 2016. Results: 43% of respondents have become surgical residents at the time they answered the poll. 56% responded that their participation in the training course helped them in the choice of speciality. 72% of respondents believe that after completing the training course, they felt more confident during laparoscopic surgery. According to 65.2%, the learning objectives have been fully achieved. Conclusions: Starting the LS learning curve in medical school through an additional course is an effective and necessary approach for the rapid and harmonious growth of young surgeons.